HUMANIZASUS : UMA AVALIAÇÃO POLÍTICA DA POLÍTICA - Furtado, Talita Teresa Gomes (2011)
The dissertation presents a study of political assessment of the National Policy on Humane Care and Management of the SUS (PNH), also called HUMANIZASUS, was drafted and introduced in 2004, for a specific Working Group organized by the Ministry of Health Research developed sought effort to analyze and clarify issues and criteria for the process of designing and engineering the policy itself. To that end, we traced the historical analysis of SUS in the context of the Brazilian health panorama from the Sanitation Movement, in order to demarcate the aspects and determining factors of the development scenario of the HNP and enable the evaluation here intended. From the historical overview tracing the origins and the humanization of the government agenda, emit judgments about the ethical and political reference considered by policy makers, and we evaluate the coherence and relevance of the proposal, through the elements which constitute its structure.